Observation of magnetic nanoparticles ring formation and dynamics with fast video camera - Bacia, Marcin; Masajada, Jan; Drobczyński, Sławomir (Photonics Letters of Poland, 2013)
The holographic optical tweezers were used to show the interaction between strongly focused laser beam and magnetic nanoparticles in ferrofluid. When the light intensity was high enough, magnetic nanoparticles were removed from the beam center and they formed a dark ring. This behavior was observed in slow motion. Creation of dark rings is a very dynamic process, which was further described in the following paper. Full Text: PDF Supplementary media files: Movie File 1 (AVI, 5.75 MB) Movie File 2 (AVI, 5.01 MB) Movie File 3 (AVI, 3.03 MB) References C. Scherer, M. F. Neto, "Ferrofluids: properties and applications", Brazilian Journal of Physics, 35, 718-727 (2005) CrossRef J. Philip, JM. Laskar, "Optical Properties and Applications of Ferrofluids-A Review", J. Nanofluids, 1, 3-20 (2012) CrossRef D. G. Grier, "A revolution in optical manipulation", Nature, 424, 21 (2003) CrossRef A. Jonas and P. Zemanek, "Light at work: The use of optical forces for particle manipulation, sorting, and analysis", Electrophoresis 29, 4813 (2008) CrossRef E. Curtis, B. A. Koss, D. G. Grier, "Dynamic holographic optical tweezers", Opt. Commun., 207, 169, (2002) CrossRef K. T. Gahagan and G. A. Swartzlander, "Optical vortex trapping of particles", Opt. Lett. 21, 827 (1996) CrossRef J. Arlt, V. Garcez-Chavez, W. Sibbett, K. Dholakia, "Optical micromanipulation using a Bessel light beam", Opt. Commun., 197, 239, (2001) CrossRef T. Sugiyama, K. Yuyama and H. Masuhara, "Laser Trapping Chemistry: From Polymer Assembly to Amino Acid Crystallization", Accounts of Chemical Research, 45 1946, (2012) CrossRef B. Hoffmann, W. Köhler, "Reversible light-induced cluster formation of magnetic colloids", J. Magn. Magn. Mater. 262, 289, (2003) CrossRef R. R. Kellner, W. Köhler, "Short-time aggregation dynamics of reversible light-induced cluster formation in ferrofluids", J. Appl. Phys. 97, 034910, (2005) CrossRef Zi-Ming Meng et al., "Effects of optical forces on the transmission of magnetic fluids investigated by Z-scan technique", J. Appl. Phys., 106, 044905, (2009) CrossRef J. Masajada, M. Bacia, S. Drobczyński, "Cluster formation in ferrofluids induced by holographic optical tweezers", Opt. Lett., 38 3910-3913 (2013) CrossRef